Determination of constitutive parameters from a Taylor test using inverse analysis (2017)
Identification of material constitutive parameters is critical for accurate representation of the mechanical behavior of materials at high strain rates. However, customary characterization procedures based on curve fitting of stress-strain curves, in some cases, are not accurate when the mechanical response exhibits strain rate dependency. In this paper, an inverse characterization technique based on the Taylor impact test is proposed. The technique uses a data reduction operator based on line moments and genetic algorithm optimization to determine the optimum constitutive parameters. Material parameters for a low carbon steel associated with the Plastic Kinematic model were determined using the proposed method.